Web services: an approach to business integration models for micro-payment. (11th September 2006) - Song, William; Chen, Deren; Chung, Jen-Yao
The introduction of the semantic web and web service technologies enables business processes, modelling and management to enter an entirely new stage. Traditional web-based business data and transactions can now be extracted to discover new business rules and strategies. Methods equipped with business policies and processes will construct services, workflows, and software functions. As a service intensive activity, micro-payment has many tasks involving different forms of services. Through analysing web service issues for micro-payment systems, we will investigate, discuss and illustrate how the web services technology support and transform the business process and integration model and produce various service flows.